Analisis Sistem Pengembangan SDM Melalui Pendekatan Training Pada Dompet Dhuafa Waspada - Zafira, Zafira; Dahrani, Dahrani (Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to determine the HR development system through a training approach at Dompet Dhuafa Waspada, the need for a training approach in developing the HR system at Dompet find out the results of the effectiveness of the training approach Dhuafa Waspada to in the HR development system at Dompet Dhuafa Waspada. The type of this research is qualitative with descriptive research method. Data collection tools in this study used observation, interviews, documentation and analyzed through data triangulation. The results show that the results of the study indicate that the system implemented in HR development is through a (contextual) training approach at Dompet Dhuafa Waspada, using development and training methods on the job training and off the job training, monitoring and evaluating as well as improving skills, competencies, employee independence with efforts to achieve company progress